2011
DOI: 10.4061/2011/240837
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Elemental Composition on the Structure, Electrochemical Properties, and Ozone Production Activity of Ti/SnO2-Sb-Ni Electrodes Prepared by Thermal Pyrolysis Method

Abstract: Ti/SnO2-Sb-Ni electrodes with various Ni- and Sb-doping levels have been prepared by dip-coating thermal pyrolysis procedure, and their simultaneous electrochemical ozone production (EOP) and oxygen evolution reaction (OER) were investigated. The effects of electrode composition on the nanostructure, morphology, electrochemical behavior, kinetic parameters, and lifetime of the electrodes were systematically studied using X-ray diffraction, scanning electron microscopy, cyclic voltammetry, linear sweep voltamme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 44 publications
(79 reference statements)
1
22
0
Order By: Relevance
“…An intriguing aspect of the material was that a very small concentration of nickel added to the mixed oxide yielded an electrode that made it possible to produce ozone at low anode potentials (2.2 V vs. Ag/AgCl) at room temperature and at relatively high current efficiencies (∼30 %) while the current efficiency was almost 0 % in the absence of nickel. Since then, several groups have studied the material and current efficiencies of up to 54 % at potentials below 3 V vs. Ag/AgCl have been reported [7,[10][11][12][13][14][15][16]. The minimum energy demand found so far is 18 kWh/kg O3 [7] which, to our knowledge, is the lowest value reported for the electrochemical formation of ozone and is moreover low enough to compete with the CCD process.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…An intriguing aspect of the material was that a very small concentration of nickel added to the mixed oxide yielded an electrode that made it possible to produce ozone at low anode potentials (2.2 V vs. Ag/AgCl) at room temperature and at relatively high current efficiencies (∼30 %) while the current efficiency was almost 0 % in the absence of nickel. Since then, several groups have studied the material and current efficiencies of up to 54 % at potentials below 3 V vs. Ag/AgCl have been reported [7,[10][11][12][13][14][15][16]. The minimum energy demand found so far is 18 kWh/kg O3 [7] which, to our knowledge, is the lowest value reported for the electrochemical formation of ozone and is moreover low enough to compete with the CCD process.…”
Section: Introductionmentioning
confidence: 90%
“…The metal salts SnCl45H2O, SbCl3 and NiCl26H2O were dissolved in alcohol to the molar ratios of 1000: (16)(17)(18)(19)(20):(2-6) (Sn:Sb:Ni) [7,[9][10][11][12][13]15]. This precursor solution is then coated on a pre-treated titanium substrate (foil or mesh) by brush, dip or spray coating.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sumanta et al [9] synthesized Pt doped SnO 2 thin films on TCO (transparent conducting oxide) substrates, and it was used as electrode to oxidize methanol, the study revealed that Pt-SnO 2 electrode is more effective for methanol electro-oxidization than pure SnO 2 . Shekarchizade et al [10] prepared Ti/SnO 2 -Sb-Ni electrodes with various Ni-and Sb-doping levels by dip-coating thermal pyrolysis procedure, the results showed that the presence of appropriate amounts of Ni and Sb can improve the electrode performance, such as EOP activity, resistance, capacitance, roughness factor and service life. Dong et al [11] studied the conductivity and stability of Bi-doped SnO 2 electrode using electrochemical method and first principle calculation, it turned out that the conductivity and stability of Bi-doped SnO 2 electrode reached best when the doping ratio is 100:8.…”
Section: Introductionmentioning
confidence: 97%
“…For Ti/SnO 2 -Sb 2 O 5 anode, 5 % of Sb dopant is an optimum concentration for electro-oxidation of 4-chlorophenol (Watts et al 2008). Addition of Ni onto TiO 2 /SnO 2 -Sb electrode yields satisfactory results (Shekarchizade and Amini 2011). Macroporous Sb-doped SnO 2 /TiO 2 nanotube electrodes have successfully been synthesized and found to display superior performance as a catalyst with regard to decreasing the toxicity of p-nitrophenol (Chai et al 2011).…”
Section: Introductionmentioning
confidence: 99%